107 Evaluating the Costs of Follow-up Imaging Protocol for Endovascularly Treated Unruptured Intracranial Aneurysms: A Multicenter Study. (August 2016) - Gupta, Raghav; Griessenauer, Christoph Johannes; Adeeb, Nimer; Moore, Justin M.; Patel, Apar S.; Juan Chua, Michelle Hui; Thomas, Ajith J.; Ogilvy, Christopher S.
Abstract : INTRODUCTION: Unruptured intracranial aneurysms (UIAs) are being detected at a greater rate. Advances in endovascular technologies have reduced procedural morbidity and mortality compared with traditional surgical clipping in a subset of these cases. Little exists in the literature identifying optimal follow-up imaging protocols for these patients. Given recent data that suggest that percent occlusion of the aneurysm at follow-up correlates strongly with the rate of rerupture, the utilization of imaging modalities that are both specific and sensitive for aneurysm detection, at the appropriate time points, is essential. Here, the authors provide a summary of the costs of 5-year follow-up imaging protocols at major academic institutions across the country. METHODS: An online survey was distributed to cerebrovascular departments at major academic centers throughout the United States, to assess imaging protocols following endovascular treatment of UIAs. RESULTS: Twenty-six responses were received. Nine (34.6%) of the centers were located in the Northeast and Southeast, each, while 4 were (15.4%) located in the Midwest. Two (7.7%) responses came from centers located in both the West and Southwest. Costs for imaging protocols following coil embolization and stent-assisted coiling range from 4064 to 30 672. For patients treated with flow diversion techniques, these costs ranged from 4064 to 46 670. Seventeen (65.3%) and 18 (69.2%) of the institutions perform a cerebral angiogram at 6-month follow-up after coil embolization and Pipeline Embolization Device installation, respectively. Twenty percent (5/25) of the respondents reported having a different imaging protocol for treated ruptured intracranial aneurysms. CONCLUSION: Significant heterogeneity in imaging follow-up protocols following endovascular treatment of UIAs exists across the country, despite limited data suggesting the benefit of particular screening regimen in the detection of recanalized aneurysms. There are significant costs associated with these protocols for patients, suggesting the need for further exploration into the optimal regimen.